Teaching effectiveness and work performance of general education instructors in a higher education institution in the Philippines - Mangila, Benjamin B. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nowadays, many people can be a teacher, but the question, if many people can be an effective teacher. As such, this study was conducted to assess the general education instructors’ teaching effectiveness and work performance in a higher education institution of Zamboanga del Sur, Mindanao, Philippines. Thirty-two part-time instructors and 194 students were selected as participants of the study. Descriptive survey was used with the questionnaire-checklist as data collection tool. The results of the study revealed that similarities existed on instructors and students’ assessments on the instructors’ teaching effectiveness in terms of commitment and work performance along with accomplishment of work, courtesy, and readiness for service. Differences also occurred on instructors and students’ assessments on instructors’ teaching effectiveness as to knowledge of the subject, teaching for independent learning, and management of learning, and on work performance as to cleanliness and orderliness of work area, and grooming and appearance. Furthermore, the results imply that instructors’ teaching effectiveness and work performance can be effectively enhanced by revisiting teacher and general education curricula to make them responsive to changing demands of the society, re-evaluating hiring and selection processes of instructors to highlight the competencies required for the work, conducting trainings and seminars regularly for instructors’ professional growth and advancement, and continuous monitoring to obtain comprehensive view of instructors’ teaching effectiveness and work performance.